Existência e configuração de ciclos limites em sistemas diferenciais planares - Schmidt, Dionatan Ricardo (2018)
In this dissertation, we present results on the existence of limit cycles in planar differential systems, configuration of such cycles and the dynamics of nonlinear systems near periodic orbits.